Exploring of two different equated instability resistance training programs on measure of physical fitness and lower limb asymmetry in pre-pubertal weightlifters - Hammami, R.; Nobari, H.; Hanen, W.; Gene-Morales, J.; Rebai, H.; Colado, J. C.; Ardigò, L. P. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Although previous research in pediatric populations has reported performance enhancements following instability resistance training, the effects of different volumes on measures of balance, strength and power and lower limb asymmetry remain unclear.